Usia pubertas dan citra tubuh terhadap perilaku seksual pranikah pada remaja putri di Yogyakarta - Rihul Husnul Juliyatmi; Toto Sudargo; Djauhar Ismail (Berita Kedokteran Masyarakat (BKM), 2018)
Age of puberty and body image to premarital sexual behavior in female adolescent In Yogyakarta PurposeThe purpose of this study was to identify the relationship between age of puberty and body image with premarital sexual behavior in young women in Yogyakarta.MethodObservational research with cross-sectional design using quantitative and qualitative approach was conducted involving 206 students in Vocational High School Yogyakarta with sampling technique purposive sampling.ResultsAs many as 28.16% of respondents are at risk of sexual pre-marriage. The age of puberty and body image has no significant relationship with premarital sexual behavior in adolescents p>0.05. Media information and peers gives the most influence to age of puberty relationship with premarital sexual behavior. Media information gives the most influence on the relationship of body image with premarital sexual behavior.ConclusionThere is no significant relationship between age of puberty and premarital sexual behavior in adolescents. There is a no significant relationship between body image and premarital sexual behavior in adolescents.